ANALISIS PENGUATAN KARAKTER RELIGUS DAN KEMANDIRIAN DALAM PEMBELAJARAN PPKN DI KELAS VII SMP NEGERI 37 MEDAN - Nababan, M. Nehemia; Meidarlin Pasaribu, Kondios; Pardede, Lukman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to analyze the strengthening of religious character and independence in Pancasila and Civic Education (PPKn) learning in Grade VII at SMP Negeri 37 Medan. Education in Indonesia aims to shape the younger generation with moral values, ethics, and social responsibility. This study employs a qualitative approach with a descriptive method. Data collection techniques include interviews, observations, and documentation.The findings of this study indicate that strengthening religious character is carried out through the integration of religious values in Civics Education (PPKn) materials, the habit of praying before and after lessons, and teachers serving as role models in their behavior. Meanwhile, the reinforcement of independence is achieved through discussion-based learning methods, case studies, and individual assignments that encourage students to think critically and make their own decisions.Supporting factors for character development include the role of teachers, school environment support, and student involvement in religious extracurricular activities. However, several challenges exist, such as students' lack of awareness, external environmental influences, and limited family support.Keywords: Character reinforcement, religious values independence Civics Education